The usefulness of a tool to assess reflection in a servicelearning experience - A-M Wium; S du Plessis (South African Medical Association, 2016)
Background. During a service-learning module, the focus is on the development of reflective competence, which is part of professional competence. The students have to reflect in a structured manner on the service-learning experience to understand and appreciate not only the module and discipline, but also their sense of personal value and social responsibility. By providing structured opportunities for reflection, deeper learning can be facilitated, which enhances competence. Do students benefit from the process of reflection and how should it be measured?Objective. To determine the usefulness of an assessment tool.Methods. A documented review of reflection journals made use of a rubric to score the structured reflection of students at a particular service-learning site. Descriptive statistics were used to analyse the data.Results. The results showed positive changes in terms of analysis, critical thinking, emotive aspects, social responsibility and self-confidence.Conclusion. Specific factors were identified that could have affected the reflections, and recommendations are made to increase the effectiveness of the assessment tool and the process of reflection.